1994
DOI: 10.1002/j.1460-2075.1994.tb06809.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific in vivo association between the bHLH and LIM proteins implicated in human T cell leukemia.

Abstract: The protein products of proto‐oncogenes implicated in T cell acute lymphoblastic leukemia include two distinct families of presumptive transcription factors. RBTN1 and RBTN2 encode highly related proteins that possess cysteine‐rich LIM motifs. TAL1, TAL2 and LYL1 encode a unique subgroup of basic helix‐loop‐helix (bHLH) proteins that share exceptional homology in their bHLH sequences. We have found that RBTN1 and RBTN2 have the ability to interact with each of the leukemogenic bHLH proteins (TAL1, TAL2 and LYL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
189
0
2

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(200 citation statements)
references
References 56 publications
9
189
0
2
Order By: Relevance
“…In addition to its E protein DNA-binding partners, recent studies have shown that the TAL1-encoded proteins can interact with the products of two genes, LMO1 and LMO2, that are themselves activated by chromosomal translocation in T-ALL (Valge-Archer et al, 1994;Wadman et al, 1994a). LMO1 and LMO2 contain tandem copies of a protein interaction motif termed the LIM domain and have each been shown to cooperate with TAL1 in inducing thymic neoplasms in bitransgenic mice (Aplan et al, 1997;Larson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its E protein DNA-binding partners, recent studies have shown that the TAL1-encoded proteins can interact with the products of two genes, LMO1 and LMO2, that are themselves activated by chromosomal translocation in T-ALL (Valge-Archer et al, 1994;Wadman et al, 1994a). LMO1 and LMO2 contain tandem copies of a protein interaction motif termed the LIM domain and have each been shown to cooperate with TAL1 in inducing thymic neoplasms in bitransgenic mice (Aplan et al, 1997;Larson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The LIM motif was found in diverse proteins, including homeodomain-containing transcription factors, cytoskeletal proteins, and other signaling proteins, which were found to be involved in cell fate determination, growth regulation, and oncogenesis (Sa nchezGarcia and Rabbitts, 1994; Dawid et al, 1995). Although most zinc ®nger motifs function by binding to speci®c DNA or RNA sequences, several lines of evidence obtained from studies on various LIM-containing proteins suggest that the LIM motifs are involved in protein-protein interactions (Schmeichel and Beckerle, 1994;Feuerstein et al, 1994;Wadman et al, 1994;Wu and Gill, 1994). Thus, the LIM motifs in LIMKs may function as binding modules to interact with other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this role in early haemopoiesis, experiments in tissue culture have provided evidence that scl is important at later stages of haemopoiesis for normal erythroid and monocytic lineage commitment and di erentiation (Green et al, 1991;Aplan et al, 1992;Tanigawa et al, 1993). Transcriptional regulation by scl may, in part, be controlled by the presence of scl-binding partners such as E12, E47 (Hsu et al, 1994) and LMO-2 (Valge-Archer et al, 1994;Wadman et al, 1994). However, the downstream target genes have not yet been identi®ed.…”
Section: Introductionmentioning
confidence: 99%